How is scientific sport research being disseminated to coaches? - Gudmundsson, H.; Sanders, R. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The main purpose of this study was to find out how sports scientists are disseminating research findings to sport coaches as a first step towards developing better ways of disseminating information in a `coach friendly` manner. It was deemed important to obtain the perspectives of both sport scientists and coaches and also to investigate the role of emerging techniques of dissemination including the World Wide Web. The use of the World Wide Web was of specific interest since these electronic tools provide search and retrieval abilities beyond anything that can be done with paper, even the best papers are of no use if they can not be located. (Boyce P.B. & Dalterio H. 1996). METHOD: Two surveys were prepared and distributed in this study - a survey of swimming coaches and a survey of sports scientists. Both surveys were prepared using software of the internet company Zoomerang.com, (www.zoomerang.com). Zoomerang.com surveys are administered through the World Wide Web and the results are compiled automatically. The surveys were completely anonymous and further analysis was conducted using SPSS. The survey for coaches was distributed to over 3000 swimming coaches in USA, Europe and Australia. The information collected included frequency of seeking scientific material related to swimming, the source of the material, the `reader friendliness` of the material, and the suitability of the World Wide Web as an information source for sport science information useful for coaches. The survey of sport scientists was distributed to over 400 sport scientists around the world. The data collected included information on frequency of submitting scientific material to sources for coaches, constraints limiting frequency of disseminating information in a form suitable for coaches, and the relative suitability of various modes of delivery including the World Wide Web. RESULTS: At the time of submitting this abstract over 1100 responses had been received from swimming coaches and surveys for sports scientists were being distributed to members of sports science organisations including the ISBS. Almost 80% of all coaches responding had a Bachelors degree (475) or post graduate qualification (350). The responses indicated that coaches were eagerly seeking information from scientists but this information was not as readily available as they would like. Other interesting results were that over 85% of coaches responding visited `often` or `very often` a web site with reader friendly scientific information. CONCLUSION: The high response rates from coaches indicated that coaches were interested and concerned about the manner in which scientific information is disseminated. It is therefore very important that researchers are ready and willing to disseminate findings on the World Wide Web and by doing so bridge the gap between sport scientists and practitioners in sports coaching.